Anthropology and the politics of alterity: A Latin American dialectic and its relevance for ontological anthropologies. (June 2022) - Lazar, Sian
Recent anglophone ontological anthropologies have an important Latin American intellectual and political history that is rarely fully acknowledged. This article outlines some of that history, arguing that debates about the politics of this 'ontological turn' should be read in the context of a tension between political economy and cosmological approaches that have been a feature of Latin American anthropology in some form since the early 20th century, and that are deeply implicated in histories of conquest and colonialism, including internal colonialism. This conceptual history helps to explain both the desire of some scholars to avoid a certain kind of politicisation and the argument that methodological and theoretical innovation within anthropology is political in itself. But it also means that ontological anthropology encounters some of the same challenges faced by indigenous movements confronted with similar choices.